(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2022)
This research aimed to know the degree of use of social networking sites in the Educational Process from the point of view of students of curricula and educational technologies at the Faculty of Education at the University of Damascus, and to study the impact of research variables on the views of students of curricula and educational technologies about the degree of use of social networking sites in the educational process, and the researcher used the descriptive approach Analytical, where a questionnaire was prepared as a tool for collecting research data, which was applied in the Faculty of Education at the University of Damascus, in April of the year 2021 AD. the original community reached 1429 male and female students, and the research sample of 246 students was selected from among the students of curricula and educational technologies, and the research reached The most important results are: that the degree of using social networking sites from the point of view of students of curricula and educational technologies was medium, and it also showed that there were no statistically significant differences between the average estimates of students of curricula and educational technologies about the degree of use of social networking sites in the education process according to the gender variable, and the presence of differences Statistically significant between the average estimates of students of curricula and educational technologies about the degree of use of social networking sites in the education process according to the variable For the school year, it also showed that there are statistically significant differences between the average estimates of students of curricula and educational technologies about the degree of using social networking sites in the education process according to the variable of using social networking sites.